Wish to conceive and concerns to develop cardiovascular complications during pregnancy in patients with Turner syndrome - Iris M. van Hagen; Anthonie L. Duijnhouwer; Marianne J. Ten Kate-Booij; Ramon H. M. Dykgraaf; Johannes J. Duvekot; Elisabeth M. W. J. Utens; Jolien W. Roos-Hesselink (Journal of Psychosomatic Obstetrics and Gynecology, 2017)
Introduction: Turner syndrome (TS) is associated with subfertility and infertility. Nevertheless, an increasing number of women become pregnant through oocyte donation. The wish to conceive may be negatively influenced by the fear of cardiovascular complications. The aim was to investigate the wish to conceive and the concerns about cardiovascular complications during pregnancy in women with TS. Methods: The patient association for TS invited all members of ≥18 years old (n = 344) to complete a specifically developed, disease-specific questionnaire, including questions about fertility, wish to conceive, attempts and concerns. Results were compared with previously published results of this questionnaire in women with congenital heart disease. Results: The questionnaire was completed by 89 women (median age 30.1 years, Q1–Q3 = 22.9–39.4). Of them, 51% had 45, X0-monosomy and 38% had ≥1 cardiac abnormality. Seventeen women (19%) had attempted to become pregnant and 12 of them succeeded to become pregnant. Women who had not undertaken attempts to conceive (81%), considered themselves mainly too young or had no partner. Of the total sample, 58% were concerned about the influence of pregnancy on their cardiovascular status. This was higher (75%) in the sample of women with TS and cardiac abnormalities, than in women with congenital heart disease from a previously published cohort (21%), (p < .001). There were no differences in concerns about pregnancy complications between women with TS who respectively had or had not attempted to become pregnant. Discussion: Women with TS, especially those with cardiac abnormalities, show serious concerns about the risks pregnancy may have. Patients should be timely counseled and specifically asked about their concerns. Psychosocial care should be provided when necessary.